Determination of Unknown Parameters of Photovoltaic Module Using Genetic Algorithm - I. M. Abdelqawee; Ayman Y. Yousef; Khaled M. Hasaneen; H. G. Hamed; Maged N. F. Nashed (Institute of Advanced Engineering and Science, 2016)
In this paper, the unknown parameters of the photovoltaic (PV) module are determined using Genetic Algorithm (GA) method. This algorithm based on minimizing the absolute difference between the maximum power obtained from module datasheet and the maximum power obtained from the mathematical model of the PV module, at different operating conditions. This method does not need to initial values, so these parameters of the PV module are easily obtained with high accuracy. To validate the proposed method, the results obtained from it are compared with the experimental results obtained from the PV module datasheet for different operating conditions. The results obtained from the proposed model are found to be very close compared to the results given in the datasheet of the PV module.